Quenching in cosmic sheets: tracing the impact of large-scale structure collapse on the evolution of dwarf galaxies. Issue 2 (22nd December 2022) - Pasha, Imad; Mandelker, Nir; van den Bosch, Frank C; Springel, Volker; van de Voort, Freeke
Abstract: Dwarf galaxies are thought to quench primarily due to environmental processes most typically occurring in galaxy groups and clusters or around single, massive galaxies. However, at earlier epochs, (5 < z < 2), the collapse of large-scale structure (forming Zel'dovich sheets and subsequently filaments of the cosmic web) can produce volume-filling accretion shocks which elevate large swaths of the intergalactic medium (IGM) in these structures to a hot ( T > 10 6 K) phase. We study the impact of such an event on the evolution of central dwarf galaxies (5.5 < log M * < 8.5) in the field using a spatially large, high resolution cosmological zoom simulation which covers the cosmic web environment between two protoclusters. We find that the shock-heated sheet acts as an environmental quencher much like clusters and filaments at lower redshift, creating a population of quenched, central dwarf galaxies. Even massive dwarfs that do not quench are affected by the shock, with reductions to their sSFR and gas accretion. This process can potentially explain the presence of isolated quenched dwarf galaxies, and represents an avenue of pre-processing, via which quenched satellites of bound systems quench before infall.